ILUSTRAXON: Semyotika sa Pahina at sa Piraso ng Komix. - Acuña, Arbeen R. (Kritika Kultura, 2018)
The paper proposes the term "ilustraxon" to describe the operation of meaning-making in "komix." In deriving the "x" from WJT Mitchell's "image x text" (2012) and coining a new concept, the ilustraxon called komix works as sublation or synthesis of "ilustracion" and "ilustrasyon." Two works of komix that pictured the well-known scene toward the end of Jose Rizal's Noli Me Tangere (1887), with Padre Damaso and Maria Clara's conversation, were read using semiotic analysis: three pages from Nakalarawang Noli Me Tangere (Illustrated Noli Me Tangere) (1956) arranged by Clodualdo del Mundo and Pedrito Reyes and illustrated by Ric Collado, and three panels from the strip "Clara, Join the Dark Side of the Force" (2014) by Emiliana Kampilan were compared and studied through Alice Guillermo's planes of semiotic analysis (2001). The first work is a key text because it is arguably one of the earliest komiks adaptations of an essential work on Philippine nationalism and the latter because it is a contemporary and intertextual appropriation of Rizal's writing. In conclusion, the similiarities of ilustraxon with Charles Sanders Peirce's dialogical sign--composed of the representamen, the interpretant, and the semiotic object--is elaborated. The paper ends with suggestions and notes that might contribute to the disciplines of translation studies and comics studies toward further studies or analyses of komix adaptations.